2016
DOI: 10.1111/hdi.12398
|View full text |Cite
|
Sign up to set email alerts
|

Dog ownership status and self‐assessed health, life‐style and habitual physical activity in chronic hemodialysis patients

Abstract: Introduction The Statement from the American Heart Association has emphasized a need for novel strategies that can reduce the risk of cardiovascular disease (CVD). Taking a dog for a walk forces its owner to take physical activity. Several studies have explored the relationship between pet ownership and CVD and most reported benefits. This issue has not been investigated in dialysis patients. The aim of the study was to analyze the influence of pet ownership on health and physical activity in hemodialysis pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…41 These interventions could be undertaken using weight machines 42,43 or resistance bands 20,44 most conveniently during dialysis. 45 Thinking out of the box and contemplating novel activities to increase physical activity for hemodialysis patients include dog ownership, 46 laughter therapy 47,48 and even intradialytic seated dancing. 49,50 Given the clear and significant physical deterioration programs to increase patient activity on and off the dialysis machine should all be considered.…”
Section: Discussionmentioning
confidence: 99%
“…41 These interventions could be undertaken using weight machines 42,43 or resistance bands 20,44 most conveniently during dialysis. 45 Thinking out of the box and contemplating novel activities to increase physical activity for hemodialysis patients include dog ownership, 46 laughter therapy 47,48 and even intradialytic seated dancing. 49,50 Given the clear and significant physical deterioration programs to increase patient activity on and off the dialysis machine should all be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the presence of a dog has a number of positive impacts on people's physical health 15 . For example, it has been reported that owning a dog leads to a 24% reduction in the risk of all‐cause mortality at all ages, 16 a 31% reduction in the risk of cardiovascular disease, 16–18 greater physical activity, 19 and greater ability to embrace a healthy lifestyle 20,21 . Just as in younger individuals, older dog owners benefit from the effects of walking a dog 22–27 .…”
Section: Introductionmentioning
confidence: 99%
“…The association between dog ownership and increased PA, primarily through dog walking, has been also confirmed in subjects with diabetes [ 28 ], cardiovascular diseases [ 29 ], breast cancer [ 30 ], in chronic hemodialysis patients [ 31 ] and in obese people who have undergone a gastric banding procedure [ 32 ].…”
Section: Introductionmentioning
confidence: 99%